Digital Wallet and Mobile Banking Adoption Among Rural Bank Customer - Parakh, Santosh; Ukhalkar, Prakash; Sanu, Leena (International Research Journal of Business Studies, 2020)
This study provides a rural viewpoint to the global research and literature on adoption of digital wallet and mobile banking among rural customer. It empirically examines the most influencing factors that stimulating to digital wallet and mobile banking user for service adoption. Primary and secondary data sources are used. A sample of 300 customers was surveyed from the rural areas of Maharashtra state, INDIA. A Simple Random Sampling method is used for selections of area from Maharashtra state and Chi-square testing was used in stated hypothesis. The study concludes that Security-Privacy, Trust and Familiarity has significant impact on Mobile banking adoption. And qualitative factors such has Prestige, Speed, Trust, Safety & Security, Easiness and Familiarity has major influence on rural customer for the adopting of Digital Wallet and Mobile banking services offered from financial institution